Optimizing Taxpayer Compliance: The Role of Socialization, Audits, and Sanctions with the Voluntary Disclosure Program (PPS) as a Moderating Factor (Survey on Individual Taxpayers (WPOP) registered at KPP Badung Utara Bali) - Puspita, Okta; Nugroho, Lucky (Baca Dulu Publisher, 2025)
This study aims to determine the effect of socialization, audit, and tax sanctions on taxpayer compliance with the voluntary disclosure program (PPS) as a moderation variable (Survey on Individual Taxpayers (WPOP) registered at KPP Badung Utara Bali. The object used in this study is Individual Taxpayers (WPOP) registered at KPP Badung Utara Bali. This study uses quantitative research methods and uses causal research design. The data collection in this study uses primary data sourced from the distribution of questionnaires distributed directly and also through google forms to individual taxpayer respondents. The determination of the number of samples was carried out using the theory of Hair, Jr. et al. (2022) which obtained the results of 125 samples. The data analysis used in this study uses SmartPLS Version 4.0 software. The results of this study show that the influence of socialization, audits and tax sanctions has a positive and significant impact on taxpayer compliance, but the existence of the Voluntary Disclosure Program (PPS) weakens the influence of socialization and tax audits on the compliance of Individual Taxpayers, while the Voluntary Disclosure Program (PPS) strengthens the influence of tax sanctions on the compliance of Individual Taxpayers.